Strengthening capacities for self-consumption in rural communities: The experience of an extension project of the National University, Costa Rica - Daly-Duarte, Carmen (2020)
At the National University of Costa Rica, there are several extension projects, which seek to generate a relationship between society and the university, in order to contribute to the joint development of communities. This is the case of the project called: “Management of Territorial Rural Development in three communities of the Canton of Sarapiquí”, which took place from 2018 to 2020. The communities that integrated the process were El Roble de La Virgen, Cureña and La Rambla. These three communities have characteristics of rurality, low rates of social development, and various climatic conditions and contexts that were addressed for capacity building.  This article integrates the axes of food security/sovereignty and local capacity building, through a series of training for the improvement of self-consumption capacities in the area of edible gardens. The workshops carried out resulted inthe participants learning about the need to make certain changes in their habitats.  This could be seen through an instrument applied to know the habits of the protagonists, who were mostly   female. Women mentioned that they bought their vegetables in the local greengrocery stores and were willing to learn how to produce their own vegetables  at home, with the improvement from the socioeconomic point of view that this can mean. The most liked products are green lettuce, sweet pepper, coriander, beetroot, celery, and chives.  It was possible to create a capacity building space, with the well-known Edible Gardens, which allowed to reuse of materials that would otherwise be  wasted. This activity  can serve as an alternative therapy, and to help people get  some of their food in a healthy and clean way.  The University has  a responsibility to be a process  facilitator, as part of the academic work, to contribute to the strengthening of communal capacities, considering the environment and local knowledge, adapting the methodologies to the different needs for a community approach focused on participatory actions.  that are present in one and between the different counties. In addition, action lines are established to improve DHL, which were validated with local actors.